Urogenital System for Women - Reyhan Julio Azwan; Bobby Indra Utama; Yusrawati yusrawati (Universitas Andalas, 2021)
Functionally, the urogenital system can be divided into two completely different components : urinary system and genital system. However, embryologically and anatomically, the two are closely related. Both originate from a single mesodermal ridge (intermediate mesoderm) along the posterior wall of the abdominal cavity, and initially, the excretory ducts of both systems enter the same cavity, the cloaca. The urogenital system is a system consisting of the urinary system which is divided into the urinary tract and the genital system. Where the urinary system is divided into the upper and lower urinary tracts. The upper urinary tract consists of the kidneys, renal pelvis and ureters, while the lower urinary tract consists of the urinary bladder and urethra. The external genital system in men and women is different, in men it consists of the penis, testes and scrotum, while in women it consists of the vagina, uterus and ovaries. The following will describe the urogenital system in women